Committed Democrats? How Trade-off Specific Cues Affect Expressions of Support for Liberal and Democratic Principles - Lukas Isermann; Lea Gärtner; Harald Schoen (Politische Vierteljahresschrift, 2024)
Abstract Democratic stability depends on citizens' willingness to support the application of liberal and democratic principles. Yet recent experimental research leaves doubt whether the high levels of abstract support for liberal democratic norms found in the literature translate to individuals defending these norms, even against their own interests. We argue that support for liberal and democratic principles involves trade-offs when people can determine the costs and benefits of these principles for their own political agendas. In consequence, their support for the application of these norms differs from their abstract support for the same principles. Using data from two surveys on German citizens' attitudes toward climate change and the COVID-19 pandemic, we show that trade-off specific cues affect people's expressions of support for liberal and democratic norms in line with their interests. Individuals who are more concerned about a~crisis are less willing to support norms that impede the implementation of their preferred policies. As support for the application of liberal and democratic norms significantly diverges from expressed levels of abstract support, the informative value of the latter regarding the stability of liberal democratic regimes is called into question. @Die Stabilität von Demokratien hängt von der Bereitschaft ihrer Bürger ab, die Anwendung liberaler und demokratischer Normen zu unterstützen. Jüngere Forschungsergebnisse mit Conjoint-Experimenten lassen jedoch Zweifel daran aufkommen, ob die in der Literatur festgestellte hohe abstrakte Unterstützung für liberal-demokratische Normen wirklich dazu führt, dass Individuen diese Normen auch gegen ihre eigenen Interessen verteidigen. Wir argumentieren, dass Menschen ihre Unterstützung für liberale und demokratische Normen anpassen, wenn Auswirkungen auf ihre eigene politische Agenda zu erwarten sind. Daher unterscheidet sich die abstrakte Unterstützung von der Unterstützung für die Anwendung derselben Normen. Anhand von Umfragedaten zur Haltung deutscher Bürger zum Klimawandel und der COVID-19-Pandemie zeigen wir, dass positionsbezogene Informationen im Fragetext die Unterstützung für liberale und demokratische Normen im Einklang mit den politischen Positionen der Befragten beeinflussen. Personen, die sich mehr Sorgen um eine der beiden Krisen machen, sind weniger bereit, Normen zu unterstützen, die die Umsetzung ihrer bevorzugten Policies behindern. Da die Unterstützung für die Anwendung liberaler und demokratischer Normen signifikant von der abstrakten Unterstützung abweicht, stellen die Ergebnisse der Studie die Aussagekraft abstrakter Unterstützungswerte für die Stabilität liberal-demokratischer Systeme in Frage.
Keywords: 330; Democratic stability; Procedural preferences; Policy preferences; Climate change; COVID-19; Demokratische Stabilität; Demokratische Verfahrenspräferenzen; Politische Präferenzen; Klimawandel